Controlling Idling Hours on Scania Dump Trucks as an effort to Fuel Efficiency and Improving Occupational Safety and Health - Amirudin, Agus; Burhanudin, Faham; Permatasari, Nurhalimah Vivid; Ariaputra, Andhika Fitri; Saptaputra, Syawal Kamiluddin (Indonesian Journal of Global Health Research, 2024)
Idling hours refer to the amount of time where a machine or vehicle is operational not active. The purpose of this research is to determine the control of Scania Dump Truck Idling Hours as an effort to fuel efficiency and improve occupational safety and health. This research method is quantitative descriptive. This research was carried out at PT. PPA Job Site MLP. The research subjects in this study were 38 Scania operating in the Engineering and Production sections as well as informants from Overall Grade, Engineering and Production. Data collection methods are document review, interviews and observation. The average use of diesel fuel in idling conditions is 2.57 liters/hour. In the period from January to February, the company experienced losses due to wasted diesel during idling hours amounting to 26,245 liters. The results of improvements that have been made to the idling hours of the DT Scania unit during the period January to April 2023 show significant development, where a decrease of 8% was obtained. Continuous monitoring needs to be carried out in order to maintain positive trends for operators and maintain employee enthusiasm.